What factor persuade Malaysians consumer to purchase smartphone? - Mad Lazim, Halim (UUM College of Business, 2015)
Mobile revolution was converting both developed and developing countries from using ordinary mobile phone to smartphone.This study seeks to identify whatfactors werepersuading Malaysian consumer to purchase smartphone.This studygatheredevidence to support research objective trough quantitative method.Total 427 respondents were participated in this study.The finding of this study reveals that multipurpose function of the smartphone such as multipurpose applications, high speed processors was highly influences Malaysians consumer to purchase this device.How ever the researcher found that the advertisement also one of the driver that influence Malaysian consumer’s intention to choose specific smartphone.